Reduction of molybdate to molybdenum blue by Klebsiella sp. strain hkeem - Lim, H. K.; Syed, Mohd. Arif; Abd. Shukor, Mohd. Yunus (Wiley, 2012)
A novel molybdate-reducing bacterium, tentatively identified as Klebsiella sp. strain hkeem and based on partial 16s rDNA gene sequencing and phylogenetic analysis, has been isolated. Strain hkeem produced 3 times more molybdenum blue than Serratia sp. strain Dr.Y8; the most potent Mo-reducing bacterium isolated to date. Molybdate was optimally reduced to molybdenum blue using 4.5 mM phosphate, 80 mM molybdate and using 1% (w/v) fructose as a carbon source. Molybdate reduction was optimum at 30 °C and at pH 7.3. The molybdenum blue produced from cellular reduction exhibited absorption spectrum with a maximum peak at 865 nm and a shoulder at 700 nm. Inhibitors of electron transport system such as antimycin A, rotenone, sodium azide, and potassium cyanide did not inhibit the molybdenum-reducing enzyme. Mercury, silver, and copper at 1 ppm inhibited molybdenum blue formation in whole cells of strain hkeem.